Electoral Populism Narratives in the Free Lunch Program: An Analysis of the Prabowo-Gibran Campaign in the 2024 Presidential Election - Surya, Dylan Maesa; Nurhandjati, Nurul (Journal Ilmu Sosial, Politik dan Pemerintahan, 2026)
The free lunch campaign promise put forward by Prabowo Subianto and Gibran Rakabuming Raka in the 2024 Presidential Election sparked debate between genuine social concern and electoral populism strategy. This study analyzes the narrative construction and meaning of this promise within the context of political competition using a qualitative approach with qualitative content analysis (QCA) of news coverage from Kompas.com and Tempo.co during the campaign period. The findings show that the program was utilized to build an empathetic image, erode the elite perception of the candidates, and create symbolic differentiation from other candidate pairs. Additionally, there was a shift in Prabowo's voter segmentation toward a grassroots base. These findings affirm that populism was practiced pragmatically as an adaptive strategy by the elite, not as a consistent ideology.